Analysis of Cash Waqf Endowment Fund as a Sharia Investment in Indonesia and Saudi Arabia - Asri Noer Rahmi; Syurmita Syurmita; Ade Wirman; Weni Hawariyuni; Heri Sudarsono (Islamiconomic : Jurnal Ekonomi Islam, 2025)
This study examines the role of cash waqf endowment funds as an Islamic investment instrument, with a comparative focus on LAZ Al-Azhar Indonesia and waqf institutions in Saudi Arabia. Cash waqf represents an innovative model of sustainable Islamic finance that integrates Sharia-compliant investment principles with broader socio-economic development objectives. This research aims to analyze the contribution of cash waqf investment funds to socio-economic outcomes, particularly income enhancement, healthcare improvement, and educational development. While also assessing their financial sustainability. Using a qualitative-descriptive and comparative approach based on financial reports and institutional data from 2022 to 2024, the findings indicate a significant increase in the implementation of productive waqf during the observed period. The results demonstrate that cash waqf funds have contributed positively to social welfare indicators, including poverty alleviation, hunger reduction, improved access to education, and the promotion of decent work opportunities. Furthermore, the integration of digital financial technology has enhanced efficiency and transparency in the collection and management of cash waqf, while simultaneously lowering entry barriers for waqif participation. The study also finds that the financial management of cash waqf institutions, particularly LAZ Al-Azhar Indonesia, reflects a high level of transparency and accountability, thereby strengthening institutional trust and sustainability. These findings highlight the strategic potential of cash waqf as a viable instrument for advancing inclusive and sustainable development within the framework of Islamic economics.